2017
DOI: 10.1016/j.ufug.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Strategic removal of host trees in isolated, satellite infestations of emerald ash borer can reduce population growth

Abstract: Emerald ash borer is an invasive beetle causing significant mortality of ash trees (Fraxinus spp.) in North America and western Russia. The invasive range has expanded to more than half of the states in the United States since the initial detection in Michigan, USA in 2002. Emerald ash borer is typically managed with a combination of techniques including surveys/trapping, insecticide treatments, host tree removal, biological control, and public education/outreach. The insect's rapid spread rate and cryptic lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…An estimated three million ash trees can be found in the seven-county Minneapolis-St Paul ("Twin Cities") metropolitan area. The first known EAB infestation in the Twin Cities was in St Paul in 2009, but it is believed that EAB arrived as early as 2004 [41].…”
Section: Methodsmentioning
confidence: 99%
“…An estimated three million ash trees can be found in the seven-county Minneapolis-St Paul ("Twin Cities") metropolitan area. The first known EAB infestation in the Twin Cities was in St Paul in 2009, but it is believed that EAB arrived as early as 2004 [41].…”
Section: Methodsmentioning
confidence: 99%
“…We used historical observations from the urban EAB infestation closest to Winnipeg in Minneapolis–St. Paul, Minnesota, USA (Fahrner, Abrahamson, Venette, & Aukema, 2017; Osthus, 2017) – to predict the distance‐dependent probabilities of EAB spread (see details in Yemshanov et al. (2019a)).…”
Section: Methodsmentioning
confidence: 99%
“…We used a conventional approach to estimate the probabilities of EAB spread to other sites as a function of distance from the infested locations (Kovacs et al, 2010;Leung, Cacho, & Spring, 2010;Prasad et al, 2010). We used historical observations from the urban EAB infestation (Fahrner et al, 2017;Venette, 2019) from the Minneapolis-St. Paul region. From these estimates, we calculated the probabilities of EAB infestation in each site.…”
Section: Estimates Of Eab Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…Because EAB was discovered only recently, we had little information about the spread of EAB in Winnipeg, so we estimated the likelihoods of introduction over distance using historical observations of the closest urban EAB infestation to Winnipeg in Minneapolis—St. Paul (Twin Cities), Minnesota [55, 56]. Evidence suggested that the pest entered the Winnipeg area six years ago, hence we used records of EAB from the Twin Cities for a six-year period starting from the oldest detection.…”
Section: Methodsmentioning
confidence: 99%